Phosphonium-Mediated Synthesis of a New Class of Indoloquinazoline Derivatives Bearing a C-12 Aryloxy Ester or Spiro-γ-lactone - Wiriya, Nittaya; Pattarawarapan, Mookda; Yimklan, Saranphong; Hongsibsong, Surat; Phakhodee, Wong (Synthesis, 2022)
Indoloquinazolines functionalized at C-12, which are structural analogs of the natural alkaloid cephalanthrin B, are readily constructed via Ph3P/I2-mediated one-pot reactions of isatins with aromatic alcohols. In the presence of excess phenols, the C-12 aryloxy ester products are obtained in moderate to good yields under mild conditions. Moreover, fused bicyclic hydroxyaryl derivatives such as 8-hydroxyquinoline give rise to novel C-12 spiro-γ-lactone derivatives. A reactive iminium cation species derived from dehydration of the C-12 hydroxy ester precursor is proposed as the transient intermediate responsible for these transformations.
Keywords: indoloquinazolines; isatin; triphenylphosphine; iodine; spirolactones; condensation